2002
DOI: 10.1557/jmr.2002.0330
|View full text |Cite
|
Sign up to set email alerts
|

Effects of manganese on microstructure and mechanical properties of A206 alloys containing iron

Abstract: The effects of Mn and Fe contents on the mechanical properties of aluminum-based A206 alloys were investigated quantitatively. Results showed that the addition of Fe caused a loss in both ductility and yield strength. Further addition of Mn could recover the ductility, but it caused a further loss in yield strength. In low-Mn alloys (0.29 wt% Mn) the primary constituent was the needle shape of Cu2FeAl7. Upon further addition of Mn, the Chinese script configuration of Mn-bearing particles formed instead. The Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 14 publications
3
19
0
Order By: Relevance
“…Combined with the morphology and EDS results, it can be found that there are three kinds of phases: dark Chinese script Al 15 (FeMn) 3 (SiCu) 2 (Į-Fe), gray platelet Al 7 Cu 2 (FeMn) (ȕ-Fe) and light Al 2 Cu networks. Besides, the volume fraction of ȕ-Fe is low due to the high addition of Mn, which is in consist with the results of Kamga et al [4] and Tseng et al [10]. in Fig.…”
Section: Resultssupporting
confidence: 90%
“…Combined with the morphology and EDS results, it can be found that there are three kinds of phases: dark Chinese script Al 15 (FeMn) 3 (SiCu) 2 (Į-Fe), gray platelet Al 7 Cu 2 (FeMn) (ȕ-Fe) and light Al 2 Cu networks. Besides, the volume fraction of ȕ-Fe is low due to the high addition of Mn, which is in consist with the results of Kamga et al [4] and Tseng et al [10]. in Fig.…”
Section: Resultssupporting
confidence: 90%
“…It has been reported that the presence of Mn reduces the detrimental effects of Fe to aluminum alloys. [17] These particles were mainly larger than 1 lm, with individual particles as large as 25 lm and clusters approaching 100 lm. TEM observations show that approximately 30 pct of the submicron particles were Al-Cu-Fe-Mn inclusions with the rest being Al-Cu-Mn dispersoids.…”
Section: Grain Morphologymentioning
confidence: 95%
“…The addition of Mn, however, reduces the detrimental effect on ductility of Al 7 Cu 2 Fe inclusions. [17] Most of the cited microstructural references were for quasi-static loading regimes, and what has been lacking is an understanding of how the dynamic behavior of a microstructurally complex aluminum alloy, such as Al 2139, can be affected at the different spatial scales that span the precipitates, the dispersoids, and the inclusions. Dynamic failure in ballistic testing can be caused by damage modes such as shear localization and bending tensile failure associated with discing failure due to high strain-rate loading as a result of projectile impact.…”
Section: Introductionmentioning
confidence: 99%
“…[9,13] To neutralize its detrimental effect, Mn is often added to transform the platelet form to Chinese script morphology, which has been thought to be less detrimental to the mechanical properties of the castings. [10][11][12] In this work, the Chinese script Al m Fe is observed to be the dominant iron-rich intermetallic phase even at a high iron level of 0.5 pct and low contents of Si (0.1 pct) and Mn (0.003 pct). The influence of the Al m Fe phase on the mechanical properties of A206 cast alloys has not been investigated yet, but it is expected that it may behave similar with the Chinese script a-Fe phase due to their similar morphologies.…”
mentioning
confidence: 95%
“…It was even reported to be the only kind of iron-rich intermetallic present in the fully solidified microstructures of the A206 family of alloys containing 0.03Fe-0.36Mn, [6] 0.07Fe-0.24Mn, [7] 0.23Fe-0.2Mn, [8] and 0.62Fe-0.8Si-0.04Mn [9] (all alloy compositions are in weight percent unless indicated otherwise). In addition to Al 7 Cu 2 Fe, a Chinese script Al-Cu-FeMn-Si intermetallic, named Mn-bearing iron intermetallic, was observed in Al-4.52Cu-0.30Fe-0.67Mn alloy by Tseng et al [10] Recently, Liu et al [11,12] systemically investigated the solidification characteristics of the ironrich intermetallics in a A206 cast aluminum alloy with 0.3Fe and found that both platelet b-Fe (including preeutectic Al 7 Cu 2 (FeMn) and eutectic Al 7 Cu 2 Fe) and Chinese script a-Fe (Al 15 (FeMn) 3 (SiCu) 2 ) may be present in the fully solidified microstructures, depending on the Mn/Fe and Si/Fe ratios. A206 cast alloys have been widely used in automotive and aerospace industries.…”
mentioning
confidence: 99%